Antimicrobial solid media for screening non‐sterile Arabidopsis thaliana seeds. Issue 4 (14th March 2020) - Behrendorff, James B.Y.H.; Borràs‐Gas, Guillem; Pribil, Mathias
Abstract : Stable genetic transformation of plants is a low‐efficiency process, and identification of positive transformants usually relies on screening for expression of a co‐transformed marker gene. Often this involves germinating seeds on solid media containing a selection reagent. Germination on solid media requires surface sterilization of seeds and careful aseptic technique to prevent microbial contamination, but surface sterilization techniques are time consuming and can cause seed mortality if not performed carefully. We developed an antimicrobial cocktail that can be added to solid media to inhibit bacterial and fungal growth without impairing germination, allowing us to bypass the surface sterilization step. Adding a combination of terbinafine (1 μM) and timentin (200 mg l −1 ) to Murashige and Skoog agar delayed the onset of observable microbial growth and did not affect germination of non‐sterile seeds from 10 different wild‐type and mutant Arabidopsis thaliana accessions. We named this antimicrobial solid medium "MSTT agar". Seedlings sown in non‐sterile conditions could be maintained on MSTT agar for up to a week without observable contamination. This medium was compatible with rapid screening methods for hygromycin B, phosphinothricin (BASTA) and nourseothricin resistance genes, meaning that positive transformants can be identified from non‐sterile seeds in as little as 4 days after stratification, and transferred to soil before the onset of visible microbial contamination. By using MSTT agar we were able to select genetic transformants on solid media without seed surface sterilization, eliminating a tedious and time‐consuming step.